2021
DOI: 10.3389/fmicb.2021.694601
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Emaravirus From Grapevine Showing Chlorotic Mottling Symptoms

Abstract: A novel negative-sense, single-stranded (ss) RNA virus was identified in a “Shennong Jinhuanghou” (SJ) grapevine showing severe chlorotic mottling symptoms by integrating high-throughput sequencing (HTS) and conventional Sanger sequencing of reverse transcription polymerase chain reaction (RT-PCR) products. The virus was provisionally named as “grapevine emaravirus A” (GEVA). GEVA had a genome comprising five genomic RNA segments, each containing a single open reading frame on the viral complementary strand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…4a,c,f). Phylogenetic analyses with known fimoviruses revealed that ArtV1 is related to Perilla mosaic virus, making it the fourth member of the divergent phylogroup IV of Fimoviridae ( i.e., a clade of phylogenetically-related fimoviruses) [62, 63] (Fig. 4i).…”
Section: Resultsmentioning
confidence: 99%
“…4a,c,f). Phylogenetic analyses with known fimoviruses revealed that ArtV1 is related to Perilla mosaic virus, making it the fourth member of the divergent phylogroup IV of Fimoviridae ( i.e., a clade of phylogenetically-related fimoviruses) [62, 63] (Fig. 4i).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with RNA1-4, from which the putative proteins derived included recognizable functional domains, RNA5 encodes a protein of unknown function. It was not unusual in other emaraviruses that the role of P5 with a similar molecular weight but no sequence homology with each other is still to be determined (Buzkan et al, 2019 ; Wang et al, 2020 ; Fan et al, 2021 ; Rabbidge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, AcCRaV and Actinidia virus 2 (AcV-2), both infecting kiwifruits, have been found in several provinces [52,54]. Further emaraviruses including JYMaV [55], PerMV [110], LiCRaV [62], Camellia chlorotic ringspot virus 1 (CaCRSV-1) and Camellia chlorotic ringspot virus 2 (CaCRSV-2) [59], PCLSaV [31], chrysanthemum mosaic-associated virus (ChMaV) [64,111], Japanese star anise ringspot-associated virus (JSARaV) [71], Vitis emaravirus (VEV) [67,68], alfalfa ringspot-associated virus (ARaV) [66], Ailanthus crinkle leaf-associated emaravirus (ACrLaV) [74] and PloAEV that infect important commercial fruits, ornamental crops and trees have been described in China and Japan. From other parts of the world there is limited information on emaraviruses diversity and distribution.…”
Section: Geographic Occurrencementioning
confidence: 99%
“…In a nursery in Liaoning (China) Fan et al [68] detected grapevine emaravirus A (GEVA) on the grapevine cultivar "Shennong Jinhuanghou" (Vitis vinifera L.) showing chlorotic mottling symptoms. GEVA contains five RNAs and could be graft-transmitted to healthy grapevines.…”
Section: Putative Emaravirusesmentioning
confidence: 99%